Nominations of personages in portrait descriptions: contrastive study (based on Ukrainian and English literary discourses) - Mykytiuk, Iryna; Oksana, Lesinska (Видавничий дім «Гельветика», 2021)
The article explores the issue of the characters’ portrait descriptions in Ukrainian (stories by Ivan Nechuy-Levytsky) and English (short stories by William Somerset Maugham) literary discourses. The current state of research of the portrait as a genre of belles-lettres discourse is described. Particular attention is focused on identification, interpretation, and contrastive analysis of the key lexemes which form the basis of the characters’ verbal portraits. The presented research is topical, since it makes an attempt at a contrastive study of literary portraiture nominations in Ukrainian and English belles-lettres texts. The undertaken contrastive analysis elucidates peculiarities of language worldviews of the speakers of the Ukrainian and the English languages. We view literary portraiture as a powerful means of verbal representation of characters both in statics and dynamics, which is achieved through skillful depiction of their distinctive features and essential characteristics.
Keywords: Portrait characteristics; characterization; literary character; literary image